2020
DOI: 10.3390/jpm10040174
|View full text |Cite
|
Sign up to set email alerts
|

Personalisation of Molecular Radiotherapy through Optimisation of Theragnostics

Abstract: Molecular radiotherapy, or targeted radionuclide therapy, uses systemically administered drugs bearing a suitable radioactive isotope, typically a beta emitter. These are delivered via metabolic or other physiological pathways to cancer cells in greater concentrations than to normal tissues. The absorbed radiation dose in tumour deposits causes chromosomal damage and cell death. A partner radiopharmaceutical, most commonly the same vector labelled with a different radioactive atom, with emissions suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Neuroblastoma is known to be a radiosensitive disease, although if the disease is localized in several different sites external beam radiotherapy is not suitable. Therefore, targeted molecular radiotherapy is a more attractive treatment option in this setting, as it delivers tumor specific radiation and can target multiple sites of disease from the same administration (8)(9)(10)(11)(12)(13)(14). Studies have shown that 85-90% of neuroblastomas express the noradrenaline transporter molecule and can be targeted with the catecholamine analog, meta-iodobenzylguanidine (mIBG), labeled with 123 I for imaging and with the β-emitter 131 I for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma is known to be a radiosensitive disease, although if the disease is localized in several different sites external beam radiotherapy is not suitable. Therefore, targeted molecular radiotherapy is a more attractive treatment option in this setting, as it delivers tumor specific radiation and can target multiple sites of disease from the same administration (8)(9)(10)(11)(12)(13)(14). Studies have shown that 85-90% of neuroblastomas express the noradrenaline transporter molecule and can be targeted with the catecholamine analog, meta-iodobenzylguanidine (mIBG), labeled with 123 I for imaging and with the β-emitter 131 I for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In addition, the combination of the gamma emitter 131 Ba for diagnosis and both alpha emitters 223/224 Ra for therapy is beneficial and leads to a matched nuclide pair 36 for a theranostic approach. 37,38…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In addition, the combination of the gamma emitter 131 Ba for diagnosis and both alpha emitters 223/224 Ra for therapy is beneficial and leads to a matched nuclide pair 36 for a theranostic approach. 37,38 Functionalized calix [4]crown ethers and their complexes with Ba 2+ and Ra 2+ are known from the literature, 24,[28][29][30]39,40 e.g., in environmental chemistry, but little is known about the complexation behaviour, the respective complex stability constants, and the in vivo behaviour of such complexes. In the past, the cavity size of calix [4]crown-6 was tested to fit best for heavier group 2 metals.…”
Section: Introductionmentioning
confidence: 99%
“…The search for more precise cancer diagnosis and treatment has led to interest in exploiting exosomes and EVs for tumor theranostics 11 , 12 . A major theranostic tool is radiopharmaceuticals that deliver radioactive particles to cancer cells for diagnostic imaging as well as to provide targeted radionuclide therapy 13 . Successful theranostic radionuclide therapy is crucially dependent on presence of abundant amounts of target molecules on the malignant cells.…”
Section: Introductionmentioning
confidence: 99%